Effect of Intraoperative Arterial Hypotension on the Risk of Perioperative Stroke After Noncardiac Surgery: A Retrospective Multicenter Cohort Study. (12th July 2021) - Wongtangman, Karuna; Wachtendorf, Luca J.; Blank, Michael; Grabitz, Stephanie D.; Linhardt, Felix C.; Azimaraghi, Omid; Raub, Dana; Pham, Stephanie; Kendale, Samir M.; Low, Ying H.; Houle, Timothy T.; Eikermann, Matthias; et al.
Abstract : BACKGROUND: Intraoperative cerebral blood flow is mainly determined by cerebral perfusion pressure and cerebral autoregulation of vasomotor tone. About 1% of patients undergoing noncardiac surgery develop ischemic stroke. We hypothesized that intraoperative hypotension within a range frequently observed in clinical practice is associated with an increased risk of perioperative ischemic stroke within 7 days after surgery. METHODS: Adult noncardiac surgical patients undergoing general anesthesia at Beth Israel Deaconess Medical Center and Massachusetts General Hospital between 2005 and 2017 were included in this retrospective cohort study. The primary exposure was intraoperative hypotension, defined as a decrease in mean arterial pressure (MAP) below 55 mm Hg, categorized into no intraoperative hypotension, short (<15 minutes, median [interquartile range IQR], 2 minutes [1–5 minutes]) and prolonged (≥15 minutes, median [IQR], 21 minutes [17–31 minutes]) durations. The primary outcome was a new diagnosis of early perioperative ischemic stroke within 7 days after surgery. In secondary analyses, we assessed the effect of a MAP decrease by >30% from baseline on perioperative stroke. Analyses were adjusted for the preoperative STRoke After Surgery (STRAS) prediction score, work relative value units, and duration of surgery. RESULTS: Among 358, 391 included patients, a total of 1553 (0.4%) experienced an early perioperative ischemic stroke. About 42% and 3% of patients had a MAP of below 55 mm Hg for a short and a prolonged duration, and 49% and 29% had a MAP decrease by >30% from baseline for a short and a prolonged duration, respectively. In an adjusted analysis, neither a MAP <55 mm Hg (short duration: adjusted odds ratio [ORadj ], 0.95; 95% confidence interval [CI], 0.85–1.07; P = .417 and prolonged duration: ORadj, 1.18; 95% CI, 0.91–1.55; P = .220) nor a MAP decrease >30% (short duration: ORadj, 0.97; 95% CI, 0.67–1.42; P = .883 and prolonged duration: ORadj, 1.30; 95% CI, 0.89–1.90; P = .176) was associated with early perioperative stroke. A high a priori stroke risk quantified based on preoperatively available risk factors (STRAS prediction score) was associated with longer intraoperative hypotension (adjusted incidence rate ratio, 1.04; 95% CI, 1.04–1.05; P < .001 per 5 points of the STRAS prediction score). CONCLUSIONS: This study found no evidence to conclude that intraoperative hypotension within the range studied was associated with early perioperative stroke within 7 days after surgery. These findings emphasize the importance of perioperative cerebral blood flow autoregulation to prevent ischemic stroke.